Selenocompostos e Covid-19: implicações na infecção - Wildner, Guilherme (2025)
The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, rapidly became a global public health problem. The virus is mainly responsible for respiratory and immunological disorders, while also affecting other systems of the body. Despite numerous studies and clinical trials, no drug has yet demonstrated proven efficacy against the disease, whose spectrum of complications remains unclear. Thus, the search for compounds effective against both infection and inflammation remains essential. Selenium (Se), a trace element, is crucial for the maintenance of health and physiological functions. In the context of COVID-19, in silico and in situ studies have demonstrated the antiviral activity of the selenium-based compound Ebselen (Eb), which significantly inhibited SARS-CoV-2 replication in Vero-6 cells and the activity of the viral proteases Mpro and PLpro. In this study, we investigated the anti-COVID-19 potential of Eb and diphenyl diselenide ((PhSe)2). Both compounds are known for their antioxidant, neuroprotective, antimicrobial, and anti-inflammatory properties in various in vivo and in vitro experimental models. We tested the effects of these selenium compounds on SARS-CoV-2 replication in Calu-3 cells exposed to the viral Spike (S) protein and viability and morphological parameters in peripheral blood mononuclear cells (PBMC) exposed to the protein. Preliminary results showed that Eb and (PhSe)2 significantly inhibited viral replication in infected Calu-3 cells. The EC50 values for Eb and (PhSe)2, calculated 24 h post-infection, were 4.3 μM and 3.8 μM, respectively. These concentrations were considered safe, as they did not alter the viability of uninfected Calu-3 cells, for which the IC50 values were 168.7 μM and 134.6 μM, respectively. Within this range, the compounds also showed no apparent toxicity to PBMCs, i.e., they did not affect cell viability, cycle progression, or morphology, nor did they induce oxidative damage or cell death. Thus, our findings demonstrate that these compounds exhibit inhibitory effects on viral replication at concentrations that are safe for human cells, making them strong pharmacological candidates for the treatment of COVID-19.